Transformation of Sabah Traditional Rice for Combating Blast Disease - Chong, Eric Tzyy Jiann; Jovita Jun Wong; Zaleha Abdul Aziz; Chia, Lock Tan; Sreeramanan Subramaniam; Mariam Abd Latip, Datin; Lee, Ping Chin (2021)
The worldwide paddy production including the Sabah traditional rice is affected by blast disease which is caused by Magnaporthe oryzae fungal infection, resulting in a reduction of 10-30% rice yield annually. Pathogenesis-related class 4 protein such as the wheatwin2 (wwin2) has been reported to significantly defend against a soil-borne fungi infection in tobacco plants, but the capability of this protein against M. oryzae infections in rice is unclear. Therefore, this study aimed to construct a plasmid containing the wwin2 gene and transform it into the Sabah traditional rice genome to combat blast disease. In brief, the wwin2 gene was synthesized and integrated into a vector using Gateway cloning technology and was transformed into the Sabah traditional rice genome via an Agrobacterium-mediated approach. This study exhibited a promising high transformation rate with more than 90% of the transformed rice calli were expressing the reporter marker, GUS. The wwin2 gene expression in the transformed rice calli was further confirmed using quantitative real-time polymerase chain reaction. In summary, this study constructed a vector containing the wwin2 gene with a high transformation rate and capable of consistently expressing GUS and wwin2 in the transformed Sabah traditional rice calli. Subsequent analyses are needed to verify the defense mechanism of the wwin2 protein towards rice blast disease.